P08.03 Separation and divorce after the diagnosis of child's brain tumor. (6th September 2019) - Sardi, I; Censullo, M; Rousseau, M; Guidi, M; Giordano, F; Fonte, C; Farina, S; Carra, F; Genitori, L
Abstract: BACKGROUND: The diagnosis of a child's brain tumor is a terrible situation for every member of the family. Numerous are the case of separations and divorces in Italy after a diagnosis of a child's cancer. In particular, it happens with parents of children affected with brain tumor, being the most frequent solid tumor and the first cause of a tumor child's death. The crisis related to the discovery of a tumor consists of four phases: shock, reaction, processing and re-orientation. It can happen that the diagnosis, experienced as a traumatic experience, can unite the family members as well as separate them. If there is already a process of family disintegration, a trauma can be a cause for breakup. The aim of our study was to investigate the possible correlation between brain tumor diagnosis in children and parental separations/divorces. MATERIAL AND METHODS: We considered 427 patients afferent from 2012 to 2018 to the Neuro-Oncology Unit of the Meyer Children's Hospital. Brain tumors are the 55–60% of all the tumors of our hospital, with an extra-regionality greater than 65%. The data analysis was conducted through information obtained directly from the families during follow-up visits or by telephone interviews. RESULTS: Consistent with literature data in our series, the most frequent brain tumors were low-grade gliomas medulloblastomas, high-grade gliomas, ependymomas, midline diffuse gliomas, craniopharyngiomas, germ cell tumors and other rare pediatric tumors. The population was divided in 16 females and 18 males from different Italian regions: 65% from Central Italy, 23% from the South and Islands, 12% from the North. Data analysis showed 34 cases of separation and/or divorce, equal to 7% of our whole population, during treatment and more frequently at the end of treatment or after death. The median age of the 34 patients at the diagnosis of brain tumor was 9.5 years (range 1–19 years), with a higher percentage of cases of separations (41%) for parents of patients aged 10 years-14 years; 7 were the cases of separation and/or divorce when the diagnosis of brain tumor was made around 12–48 months after the child birth. CONCLUSION: The diagnosis of a child's brain tumor can generate stress in the family leading to different reactions, such as conflicts between parents or a real family crisis. The results of our study suggest a possible correlation between the diagnosis of a child's brain tumor and the cases of separation and/or divorce. High risk medulloblastomas and high-grade gliomas that are likely to have a shorter path due to the unfavorable prognosis of the disease, appear to be the pathologies more often related to situations of family disputes. However, further investigations are necessary to verify the trend emerged from our study respect to the normal population.